Peyronie's Disease and Autoimmunity—A Real-Life Clinical Study and Comprehensive Review. (1st April 2015) - Ventimiglia, Eugenio; Capogrosso, Paolo; Colicchia, Michele; Boeri, Luca; Serino, Alessandro; La Croce, Giovanni; Russo, Andrea; Capitanio, Umberto; Briganti, Alberto; Cantiello, Francesco; Mirone, Vincenzo; Damiano, Rocco; et al.
Abstract: Introduction: Although heavily investigated over the last decades, Peyronie's disease (PD) pathogenesis remains unclear. Aim: We sought to investigate the association between PD and autoimmune diseases (ADs) in men seeking medical help for sexual dysfunction in the real-life setting. Methods: Complete sociodemographic and clinical data from a homogenous cohort of 1, 140 consecutive Caucasian–European men were analyzed. Health-significant comorbidities were scored with the Charlson Comorbidity Index and ADs were stratified according to International Classification of Diseases, Ninth Revision classification. Main Outcome Measures: Descriptive statistics and multivariate logistic regression models tested the association between ADs and PD. Results: PD was diagnosed in 148 (13%) of the 1, 140 men; of PD patients, 14 (9.5%) had a comorbid AD; conversely, the rate of ADs in non-PD patients was significantly lower (χ 2 = 24.7; P < 0.01). Both patient age and AD comorbidity achieved multivariable independent predictor status for PD (odds ratio [OR]: 1.05; P < 0.01 and OR: 4.90; P < 0.01, respectively). Conclusions: Our observational findings showed that ADs are highly comorbid with PD in a large cohort of same-race individuals seeking medical help for sexual dysfunction in the real-life setting.